2001
DOI: 10.2337/diabetes.50.9.2040
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Metallothionein in Pancreatic β-Cells Reduces Streptozotocin-Induced DNA Damage and Diabetes

Abstract: The release of reactive oxygen species (ROS) has been proposed as a cause of streptozotocin (STZ)-induced ␤-cell damage. This initiates a destructive cascade, consisting of DNA damage, excess activation of the DNA repair enzyme poly(ADP-ribose) polymerase, and depletion of cellular NAD ؉ . Metallothionein (MT) is an inducible antioxidant protein that has been shown to protect DNA from chemical damage in several cell types. Therefore, we examined whether overexpression of MT could protect ␤-cell DNA and thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 47 publications
3
116
0
Order By: Relevance
“…[32][33][34][35][36][37][38] In the present study, KIOM-79 was found to decrease intracellular ROS levels, cellular DNA damage, and the lipid peroxidation that is induced by STZ. The cells exposed to STZ exhibited the distinct morphological features of apoptosis, including morphological changes and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 71%
“…[32][33][34][35][36][37][38] In the present study, KIOM-79 was found to decrease intracellular ROS levels, cellular DNA damage, and the lipid peroxidation that is induced by STZ. The cells exposed to STZ exhibited the distinct morphological features of apoptosis, including morphological changes and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 71%
“…Scale bar, 10 µm. Magnification, 40× insulin concentration nor insulin gene expression in islets was altered by overexpressing catalase by up to 50-fold [9], two forms of metallothionein by up to 30-fold [9,42] or three forms of superoxide dismutase enzymes by up to 10-fold [5,7]. Furthermore, overproduction of metallothionein and catalase in beta cells actually accelerated cytokineinduced beta cell death [9].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to IL-1β resulted in a small further up-regulation of two subclasses of GST in both phenotypes, whereas GP (FC −1.3) was exclusively down-regulated in the beta cell phenotype following IL-1β exposure (Panel B). Downregulation of metallothionein-1 and 2 (FC −2.2, Panel A) may also render the beta cells susceptible to the toxic effects of IL-1β, since it has been shown that over-expression of metallothionein in beta cells reduces streptozotocin-induced DNA damage and diabetes [15]. Exposure to IL-1β resulted in further downregulation of metallothionein-1 and 2 in both phenotypes although significantly (p<0.001) lowest in the beta-cell phenotype (FC −4.7 vs FC −2.2; Panel B).…”
Section: Glycolysis and Energy Generationmentioning
confidence: 99%
“…Destruction of the beta cells has been associated with induction of highly reactive agents like oxygen-derived free radicals and nitric oxide (NO) [10], increased apoptosis [11], decreased insulin production and release [12] and decreased mitochondrial function [12]. Stimulation or over-expression of different defence mechanisms has been demonstrated to protect beta cells against the toxic effect of cytokines, streptozotocin, NO or reactive oxygen species [13,14,15].…”
mentioning
confidence: 99%